The Utilization of Canva in Project Based Learning (PjBL) to Enhance the Students' Writing Skills. - Maya Ulyani; Widuri Indah Dwi Jayanti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research was intended to find out the utizilation of Canva for education to enhance the students' writing skills in a Project-Based learning among the students in Culinary Program Vocational High School. In this research, a PJBL was conducted to close the gap and enhance the students' writing skills in writing an exposition text using Canva for education. A Descriptive qualitative method was proposed to investigate the problem of the research. The data was collected using observation and questionnaire, and the researcher used purposive sampling to select the data. Thirty-six students in grade 11 are in the Culinary Program of SMKN 6 Yogyakarta as the research data. The results show project-based learning by integrating the Canva app successfully and using the Canva application in the PjBL model to enhance the student's writing skills, especially in Exposition text. It is also supported by the questionnaire of students' perception of using the Canva application. Most of the students agree that using Canva in writing Project of Exposition text can ease their understanding of the learning material, explore their idea and creativity and enable them to focus more on the writing project.